Mutant pfcrt "SVMNT" haplotype and wild type pfmdr1 "N86" are endemic in Plasmodium vivax dominated areas of India under high chloroquine exposure - Mallick Prashant K; Joshi Hema; Valecha Neena; Sharma Surya K; Eapen Alex; Bhatt Rajendra M; Srivastava Harish C; Sutton Patrick L; Dash Aditya P; Bhasin Virendra K (Malaria Journal, 2012)
Abstract Background Chloroquine resistance (CQR) phenotype in Plasmodium falciparum is associated with mutations in pfcrt and pfmdr-1 genes. Mutations at amino acid position 72-76 of pfcrt gene, here defined as pfcrt haplotype are associated with the geographic origin of chloroquine resistant parasite. Here, mutations at 72-76 and codon 220 of pfcrt gene and N86Y pfmdr-1 mutation were studied in blood samples collected across 11 field sites, inclusive of high and low P. falciparum prevalent areas in India. Any probable correlation between these mutations and clinical outcome of CQ treatment was also investigated. Methods Finger pricked blood spotted on Whatman No.3 papers were collected from falciparum malaria patients of high and low P. falciparum prevalent areas. For pfcrt haplotype investigation, the parasite DNA was extracted from blood samples and used for PCR amplification, followed by partial sequencing of the pfcrt gene. For pfmdr-1 N86Y mutation, the PCR product was subjected to restriction digestion with AflIII endonuclease enzyme. Results In 240 P. falciparum isolates with reported in vivo CQ therapeutic efficacy, the analysis of mutations in pfcrt gene shows that mutant SVMNT-S (67.50%) and CVIET-S (23.75%) occurred irrespective of clinical outcome and wild type CVMNK-A (7.91%) occurred only in adequate clinical and parasitological response samples. Of 287 P. falciparum isolates, SVMNTS 192 (66.89%) prevailed in all study sites and showed almost monomorphic existence (98.42% isolates) in low P. falciparum prevalent areas. However, CVIETS-S (19.51%) and CVMNK-A (11.84%) occurrence was limited to high P. falciparum prevalent areas. Investigation of pfmdr-1 N86Y mutation shows no correlation with clinical outcomes. The wild type N86 was prevalent in all the low P. falciparum prevalent areas (94.48%). However, mutant N86Y was comparably higher in numbers at the high P. falciparum prevalent areas (42.76%). Conclusions The wild type pfcrt gene is linked to chloroquine sensitivity; however, presence of ...